TERBIUM AND BARIUM CODOPED MESOPOROUS SILICA NANOPARTICLES WITH ENHANCED OPTICAL PROPERTIES - Zhumanova, Kamila; Akhmetzhanov, Nursalim; Kang, Moon Sung; Molkenova, Anara; Raja, Iruthayapandi Selestin; Kim, Ki Su; Han, Dong-Wook; Atabaev, Timur Sh. (Materials Letters, 2022)
In this study, we showed for the first time that barium (Ba) codoping improves the luminescent properties of terbium (Tb)-doped SiO2 nanoparticles (NPs). In particular, the quantum yield (QY) of SiO2-Ba,Tb NPs was found to be ~10.7%, whereas the QY of bare SiO2-Tb NPs was only ~4.3%. Several mechanisms for luminescence enhancement have been proposed. We strongly believe that this methodology can be used to create alternative silica-based NPs with improved optical characteristics.
Keywords: Type of access: Open Access; Nanoparticles; Porous materials; Optical materials and properties; Luminescence